PERALIHAN KREDIT MODAL KERJA PERMANEN MENJADI KREDIT UMUM PADA LEMBAGA PEMBIAYAAN BANK PEMBANGUNAN DAERAH BALI CABANG NEGARA KABUPATEN JEMBRANA - Dwi Mei Anggara, I Made; Sukihana, Ida Ayu (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 11, November 2013, 2013)
This paper was written under the title Transitional Working Capital Loans from Credit Becomes Permanent General on Bank Daerah Bali Cabang Negara Kabupaten Jembrana. With a view to the consideration know Bank Pembangunan Daerah Bali Doing Transition Working Capital Loan from a Credit Permanent General, the author uses empirical legal research methods, so it concluded that in this transition to avoid the risk of credit losses from Bank Pembangunan Daerah Bali.
Keywords: Transition, Credit, Bank Pembangunan daerah Bali